Genetic substructure and admixture as important factors in linkage disequilibrium‐based estimation of effective number of breeders in recovering wildlife populations. Issue 24 (7th November 2017) - Kopatz, Alexander; Eiken, Hans Geir; Schregel, Julia; Aspi, Jouni; Kojola, Ilpo; Hagen, Snorre B.
Abstract: The number of effective breeders ( N b ) and effective population size ( N e ) are population parameters reflective of evolutionary potential, susceptibility to stochasticity, and viability. We have estimated these parameters using the linkage disequilibrium‐based approach with LDNE through the latest phase of population recovery of the brown bears ( Ursus arctos ) in Finland (1993–2010; N = 621). This phase of the recovery was recently documented to be associated with major changes in genetic composition. In particular, differentiation between the northern and the southern genetic cluster declined rapidly within 1.5 generations. Based on this, we have studied effects of the changing genetic structure on N b and N e, by comparing estimates for whole Finland with the estimates for the two genetic clusters. We expected a potentially strong relationship between estimate sizes and genetic differentiation, which should disappear as the population recovers and clusters merge. Consistent with this, our estimates for whole Finland were lower than the sum of the estimates of the two genetic clusters and both approaches produced similar estimates in the end. Notably, we also found that admixed genotypes strongly increased the estimates. In all analyses, our estimates for N e were larger than N b and likely reflective for brown bears of the larger region of Finland and northwestern Russia. Conclusively, we find that neglecting genetic substructure may lead to a massive underestimation of N b and N e . Our results also suggest the need for further empirical analysis focusing on individuals with admixed genotypes and their potential high influence on N b and N e . Abstract : The number of effective breeders ( N b ) is a crucial parameter in conservation, as it is closely coupled with the long‐term survival of a population. Many recovering populations are still structured following fragmentation. We estimated N b for the recovering brown bear ( Ursus arctos ) population in Finland, and our study suggest that tracing N b in a natural system should account for population subdivision and admixture in order to reduce potential estimation biases.